The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5489/cuaj.777
|View full text |Cite
|
Sign up to set email alerts
|

Update on the management of non-muscle invasive bladder cancer

Abstract: Non-muscle invasive bladder cancer (NMIBC) is a heterogeneous population of tumours accounting for 80% of bladder cancers. Over the years, the management of this disease has been changing with improvements in results and outcomes. In this review, we focus on the latest updates on the management of NMIBC.Can Urol Assoc J 2010;4(1):56-64 RésuméLe cancer de la vessie sans envahissement musculaire est un groupe hétérogène de tumeurs représentant 80 % des cancers de la vessie. Au fil des années, la prise en charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 132 publications
(137 reference statements)
2
80
1
Order By: Relevance
“…This result is consistent with the previous studies that have reported positive association between socio-economic factors and life satisfaction. Sacks, Stevenson and Wolfers (2010) and Aldousari and Kassouf (2010) document a positive relationship between subjective wellbeing and education, income and social relationships. Similarly, Frey (2008) found demographic variables like, income, marriage, education and religiousity to be significantly associated with individual happiness.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the previous studies that have reported positive association between socio-economic factors and life satisfaction. Sacks, Stevenson and Wolfers (2010) and Aldousari and Kassouf (2010) document a positive relationship between subjective wellbeing and education, income and social relationships. Similarly, Frey (2008) found demographic variables like, income, marriage, education and religiousity to be significantly associated with individual happiness.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high recurrence rate, bladder cancer has the highest lifetime treatment cost per patient of all cancers [2,3] and requires frequent surveillance. White light cystoscopy (WLC) is the standard imaging tool for detection, resection and surveillance of bladder cancer; however, WLC has well-recognized shortcomings that can adversely impact treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure is performed by preinstilling 5-aminolevulinic acid or hexaminolevulinate in the bladder 30 to 60 minutes before using ultraviolet/blue light cystoscopy. 126 The chemicals are concentrated in the malignant urothelial cells, which are then easily identified with blue light cystoscopy. A meta-analysis using raw data from prospective studies on 1345 patients with known or suspected nonmuscleinvasive bladder cancer compared blue light cystoscopy with white light cystoscopy.…”
Section: Blue-light/fluorescence Cystoscopy Formentioning
confidence: 99%
“…125 Because 50% to 70% of superficial urothelial carcinomas recur, there has been a high demand for better detection techniques. 126 Fluorescence/blue light cystoscopy is a relatively new diagnostic and therapeutic technique that is performed at our institution. In contrast to regular white light cystoscopy where some tumors may be missed because of their small size, blue light cystoscopy, which is an enhanced imaging procedure, helps urologists identify bladder lesions/tumors of any size more easily by using Cysview (hexaminolevulinate hydrochloride, Photocure ASA, Oslo, Norway), which turns malignant cells in the bladder bright pink or red under a blue light (Figure 11, A through F).…”
Section: Blue-light/fluorescence Cystoscopy Formentioning
confidence: 99%